Are complementary and alternative medicines effective in treating insomnia?. Issue 10 (October 2015) - Welch, Sarah Kay; Vaughan, Erin; Hunter‐Smith, Daniel
Abstract : Evidence‐Based Answer : In children with delayed sleep phase disorder, total sleep time increased by 28 minutes and sleep onset latency decreased by 16 minutes with melatonin (SOR: C, disease‐oriented outcome). Yoga and tai chi may reduce insomnia. Acupuncture and L‐tryptophan studies have had mixed results. Kava and valerian root are not likely effective (SOR: C, systematic reviews of poor‐quality RCTs).